small and historic - Grigoryeva, Elena (project baikal, 2019)
… If till blood the cloth has been worn, I will patch with the golden patches. That the good Lord will notice it more. Vladimir Vysotsky, The Cupolas © Ilya Shambat. Translation, (n.d.) Small towns with deep-rooted history, cozy and diverse, each with its own appearance – this image, like a lasting impression of childhood, makes you return again and again. Like a drop of water can mirror the sky, small towns reflect the nature and fate of the big country, millions of families, vast territories… Our focus on small towns and historic settlements was definitely stimulated by the 5-year federal competition “Comfortable Urban Environment”. Two annual rounds have already been held. Together with paying attention to the environment, we should proceed from the general to the particular. Our government should focus on strengthening of the settlement fabric and town planning. There are a lot of problems facing small towns, which should be solved comprehensively, instead of tinkering at the margins. From a strategic point of view, it is necessary to think of restoration of the network of small towns – this is the only way to ensure connectivity of sparsely-populated territories. Revitalization of small towns basing on new principles of socio-economic, technological and infrastructure-planning organization becomes more relevant with each passing year. Meanwhile, the situation becomes more disturbing. The flood has covered small towns in Siberia and the Far East. They cannot do without outside help, and the urgent help has come. However, it is obvious that the disaster becomes systemic.